An analysis of TIMSS 2015 science reading demands - Van Staden, Surette; Graham, Marien Alet; Harvey, J.C. (Perspectives in education, 2020)
This study investigated the reading demands of restricted-use items1 administered to South African Grade 9 learners as part of the Trends in International Mathematics and Science Study (TIMSS) 2015. The method proposed by Mullis, Martin and Foy (2013) was used to categorise items into low, medium and high readability groups. The Knowing domain contained mostly low readability items, the Applying domain was almost equally medium and high readability items, with the Reasoning domain containing mostly high readability items. Results show significant differences between the percentage correctly answered between the low and high categories and between the medium and high categories. However, the full impact of reading demand on performance cannot be fully analysed without cross-reference to English proficiency. Nevertheless, the higher the readability, the greater the chance for learners to answer incorrectly. A continued expected low performance for most South African learners is implied.